Enhancing Engineering Competencies through Industry-Education Integration: Evidence from an Industrial Internet Talent Cultivation in Chinese Application-oriented Undergraduate University - Yanan, Qian; Wai Yie, Leong (INTI International University, 2025)
As a result of the integration of new information technologies and manufacturing, the Industrial Internet has raised new requirements for applied talent cultivation. This study, based on Chongqing Institute of Technology, explores practical pathways under the industry-education integration model. Through school-enterprise collaboration, the talent training plan was revised, courses like “Industrial Internet Technology” and “Industrial APP Development” were added, and enterprise cases were integrated into teaching. Co-built laboratories introduced enterprise-used equipment and supported innovation through secondary development. In the past two years, leading to the completion of five equipment upgrade projects based on enterprise feedback. Practical teaching capabilities were enhanced via teacher enterprise rotations and dual-qualified training. Students' hands-on abilities were strengthened through certificate-integrated courses and project-based practices, improving the high-quality employment rate to 32% and provincial-level competitions awards to 17%. However, challenges remain in interdisciplinary skill development, deeper integration of professional and specialized education, and rapid iteration of teaching resources. Future efforts should focus on optimizing curricula and building dynamic adjustment mechanisms to meet technological evolution. This study offers practical insights for Industrial Internet talent development in application-oriented undergraduate universities